PENGEMBANGAN MEDIA PEMBELAJARAN BIG BOOK PADA MATERI BANGUN DATAR BERBASIS JAJANAN PASAR DI KELAS IV SEKOLAH DASAR - Sri Amanda Putri; Nurjannah Nurjannah (STKIP Subang, 2024)
This development research aims to (1) Develop Big Book learning media for class IV flat shape material at SD Negeri 104248 Beringin, (2) To determine the feasibility of Big Book learning media for flat shape material for class IV at SD Negeri 104248 Beringin. This research is a type of ADDIE development research which consists of 5 stages but the researcher limits this research to 3 stages, namely Analysis, Design and Development. The subjects in this research are media expert validators, material experts and learning expert. The instrument used to collect data is a questionnaire. The data analysis technique used in this research is the Likert scale. Based on analysis of data obtained through validation tests by media experts, material experts and learning experts. The validation results by media experts were 92% in the Very Eligible category. The validation results by material experts were 81.25%, including the Very Eligible category. The validation results by learning experts were 94% in the Very Appropriate category. Based on the percentage results from media experts, material experts and learning experts, the assessment obtained from the expert review can be said that the Big Book media on flat-based material based on market snacks developed is